PROBLEMS OF FINANCING INNOVATIVE ACTIVITY IN RUSSIA AT THE PRESENT STAGE - O. Demenko (Publishing House of the State University of Management, 2019)
Innovations are an integral part of the economic development not only of individual enterprises, but also of the country as a whole. In this regard, it is important to allocate properly financial resources aimed at maintaining and developing innovative activities. Searching and selection of methods for financing innovations should be carried out taking into account external and internal factors, the neglect of which leads to a lack of financial resources and freezing projects at the initial stages for individual companies and technological, raw or financial dependence on foreign investors for the country.